Disintegration of waste sludge as an element bio-circular economy in waste water treatment plant towards carbon recovery for biological nutrient removal. (September 2022) - Zubrowska-Sudol, Monika; Walczak, Justyna; Piechota, Grzegorz
Graphical abstract: Highlights: Biocircular economy of excess sludge via disintegration process was investigated. Disintegrated excess sludge as a source of C to increase N and P removal was used. N and P removal depended on energy densities at which C was produced. Increase of combined N and P removal was obtained at 70 kJ/L and 210 kJ/L. Decline in efficiency of N and COD removal was observed at 280 kJ/L. Abstract: The goal of the study was to evaluate the possibility of use of disintegrated excess sludge to enhance combined biological nutrient removal from wastewater. In the experiment lasting 295 days four runs were performed. Effectiveness of contaminants removal in sequencing batch reactor without and with applying sludge subjected previously to hydrodynamic disintegration at three energy density (ƐL ) levels was analysed. It was shown that ƐL is a crucial parameters responsible for the characteristics of disintegrated sludge applied as a carbon source for biological nutrient removal. Using sludge disintegrated at 70 and 210 kJ/L the increase in effectiveness of N and P removal was noted, averagely by 16.1 % (N removal) and 70.3 % (P removal) at ƐL  = 70 kJ/L and by 17.8 % and 63.1 % at ƐL  = 210 kJ/L. On the contrary, use of sludge disintegrated at ƐL  = 280 kJ/L caused decline in N removal by averagely 12.8 %, what was a consequence of nitrification failure.